LGR4 and Its Role in Intestinal Protection and Energy Metabolism - Li, Ziru; Zhang, Weizhen; Mulholland, Michael W. (Frontiers in Endocrinology, 2015)
Leucine-rich repeat-containing G protein-coupled receptors (LGRs) were identified by the unique nature of their long leucine-rich repeat extracellular domains. Distinct from classical G protein-coupled receptors which act via G proteins, LGR4 functions mainly through Wnt/β-catenin signaling to regulate cell proliferation, differentiation, and adult stem cell homeostasis. LGR4 is widely expressed in tissues ranging from the reproductive system, urinary system, sensory organs, digestive system, and the central nervous system, indicating LGR4 may have multiple functions in development. Here we focus on the digestive system by reviewing its effects on crypt cells differentiation and stem cells maintenance, which are important for cell regeneration after injury. Through effects on Wnt/β-catenin signaling and cell proliferation, LGR4 and its endogenous ligands, R-spondins, are involved in colon tumorigenesis. LGR4 also contributes to regulation of energy metabolism, including food intake, energy expenditure and lipid metabolism, as well as pancreatic β-cell proliferation and insulin secretion. This review summarizes the identification of LGR4, its endogenous ligand, ligand-receptor binding and intracellular signaling. Physiological functions include intestinal development and energy metabolism. The potential effects of LGR4 and its ligand in the treatment of inflammatory bowel disease, chemoradiotherapy induced gut damage, colorectal cancer and diabetes are also discussed.